2015
DOI: 10.1051/0004-6361/201527131
|View full text |Cite
|
Sign up to set email alerts
|

A tunnel and a traffic jam: How transition disks maintain a detectable warm dust component despite the presence of a large planet-carved gap

Abstract: Context. Transition disks are circumstellar disks that show evidence of a dust cavity, which may be related to dynamical clearing by embedded planet(s). Most of these objects show signs of significant accretion, indicating that the inner disks are not truly empty, but that gas is still streaming through to the star. A subset of transition disks, sometimes called pre-transition disks, also shows a strong near-infrared excess, interpreted as an optically thick dusty belt located close to the dust sublimation rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 70 publications
5
77
0
Order By: Relevance
“…Inside the pressure bump generated by a Jupiter-mass planet in 2D simulations of a disc with α = 0.001 and H/r = 0.05, the maximum ∆v/c s = 0.66. This leads to a critical Stokes number of τ f = 7.5 × 10 −4 , in agreement with previous studies including diffusion, see for example Pinilla et al (2016), where very small particles can drift through the pressure bump generated by large planets. Adding the effects of particle diffusion in 2D disc simulations, Ataiee et al (2017, in prep) found that diffusion can increase the pebble-isolation mass, in agreement with Pinilla et al (2012) and our estimates.…”
Section: Diffusion Of Dust Particlessupporting
confidence: 91%
See 3 more Smart Citations
“…Inside the pressure bump generated by a Jupiter-mass planet in 2D simulations of a disc with α = 0.001 and H/r = 0.05, the maximum ∆v/c s = 0.66. This leads to a critical Stokes number of τ f = 7.5 × 10 −4 , in agreement with previous studies including diffusion, see for example Pinilla et al (2016), where very small particles can drift through the pressure bump generated by large planets. Adding the effects of particle diffusion in 2D disc simulations, Ataiee et al (2017, in prep) found that diffusion can increase the pebble-isolation mass, in agreement with Pinilla et al (2012) and our estimates.…”
Section: Diffusion Of Dust Particlessupporting
confidence: 91%
“…This mechanism allowed the small particles to move across the pressure bump generated by the planet in Pinilla et al (2016), while our simulations show an effective trapping of small particles as a result of the lack of diffusion. The difference of Pinilla et al (2016) to is probably related to different prescriptions of diffusion. We therefore estimate the effects of diffusion in the following for the pebble-isolation mass.…”
Section: Diffusion Of Dust Particlesmentioning
confidence: 70%
See 2 more Smart Citations
“…Zakhozhay ing of the vertical disc wall at the outer edge of the gap. Pinilla et al (2016) show that discs with massive planets lose the near infrared excess after a few Myrs and their SEDs look like true transition discs, while SEDs of the discs with less massive planets look like pre-transition disc SEDs for most of their remaining lifetimes.…”
Section: Introductionmentioning
confidence: 91%